Knowledge, Attitude and Practice towards Religious Obligations among Healthcare Workers in Hospital Langkawi, Malaysia - Hafiz, J; Dzulkhairi, MR; Shamsir MA.; Abu, N (Int Islamic Univ Malaysia, Kulliyyah Medicine, 2024)
Indexed by WOS/ Scopus